1996
DOI: 10.1080/15216549600201141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 137Cs‐ and 241Am‐binding sites in the oyster crassostrea gigas

Abstract: The subcellular distribution and binding of 241Am and 137Cs in the visceral mass of the oyster Crassostrea gigas were investigated following exposure to sea water contaminated with these radionuclides. 241 Am was predominantly sequestered by the lysosomal system. Approximately, 10% of 241Am was associated with soluble macromolecules. 241Am was bound to lipofuscin, ferritin and to unidentified ligands of 60 to 15 kdaltons mol. wt. No evidence was found for binding of 241Am to metallothionein synthesized de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Cr, Co, Zn, Cd and 134 Cs were mainly found in the cytosolic fraction (30-87%) whereas 110m Ag and 241 Am were mainly associated with membranes and organelles (65-96%). These results are in agreement with those reported for other bivalves from temperate waters, e.g., the scallop Chlamys varia (Bustamante and Miramand in press) and the oyster Crassostrea gigas (Milcent et al 1996).…”
Section: Resultssupporting
confidence: 92%
“…Cr, Co, Zn, Cd and 134 Cs were mainly found in the cytosolic fraction (30-87%) whereas 110m Ag and 241 Am were mainly associated with membranes and organelles (65-96%). These results are in agreement with those reported for other bivalves from temperate waters, e.g., the scallop Chlamys varia (Bustamante and Miramand in press) and the oyster Crassostrea gigas (Milcent et al 1996).…”
Section: Resultssupporting
confidence: 92%
“…Pead et al 1995, and it has also been shown that transuranium elements such as Am, Cm, Cf and Pu are associated with the cytosolic ferritin in mammals and in marine invertebrates (Stover et al 1970, Bruenger et al 1976, Galey e t al. 1983, Goudard et al 1991, Milcent et al 1996. Thus, some authors have suggested that ferritin may be a general metal detoxicant protein carrier (Joshi & Zimmerman 1988, Joshi et al 1989, Muller et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…It can bind various metals on different types of sites: within the cavity, near the inner channel openings or the outside of apoferritin (Price & Joshi 1983, Pead et al 1995. Ferritin can also bind transuranium elements (Goudard et al 1991, Milcent et al 1996 Po is probably able to bind to these different sites present on ferritin and perhaps also to the iron core of the protein. Amino acid analysis showed very small amounts of cysteinyl residues in the ferritins of mackerel and oyster.…”
Section: Sephacryl S300 Fractionsmentioning
confidence: 99%